2009
DOI: 10.1016/j.rmed.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Altered ventilatory responses to exercise testing in young adult men with obstructive sleep apnea

Abstract: The VO(2) response to exercise did not differ between groups. The V(E), V(E)/VCO(2), V(E)/VO(2) were higher (p< 0.05, 0.002, and p<0.02, respectively) in the OSA group across all workloads. The V(E)/VCO(2) slope was greater in the OSA group (p<0.05). The V(E)/VCO(2) slope and AHI were significantly correlated (r=0.56, p<0.03). Thus, young, overweight men with OSA exhibit increased ventilatory responses to exercise when compared to overweight controls. This may reflect alterations in chemoreflex sensitivity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…This finding is in agreement with a previous study (Hargens et al, 2009). However, other studies reported similar V'E/V'CO 2 and V'E/V'O 2 at maximal exercise compared to OSA patients (Innocenti Bruni, Gigliotti, & Scano, 2012;Kline et al, 2013;Lin et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding is in agreement with a previous study (Hargens et al, 2009). However, other studies reported similar V'E/V'CO 2 and V'E/V'O 2 at maximal exercise compared to OSA patients (Innocenti Bruni, Gigliotti, & Scano, 2012;Kline et al, 2013;Lin et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Mechanisms responsible for reduced V'O 2max in OSA patients remain unclear. One potential contributing factor is hypoxia-induced oxidative stress, which leads to mitochondrial damage (Ryan et al, 2005) and/or decreases in number of type I fibers and mitochondria (Nanas et al, 2010), ultimately resulting in deficit in oxidative capacity (Hargens et al, 2009). In OSA patients, an increased sympathetic drive from arousal during sleep may induce increased catecholamine release during vigorous exercise (Nanas et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiopulmonary exercise testing (CPET) is used to differentiate the etiology of exercise limitation as follows: cardiac, pulmonary, or resulting from muscle dysfunction [15][16][17][18][19]. Previous studies evaluating exercise limitation in OSA have shown improvements in cardiac dysfunction and CPET performance after 8 weeks of nasal CPAP (nCPAP) treatment [20].…”
Section: It Was Presented At; 1-european Respiratory Society Annual Cmentioning
confidence: 99%